A methodology for process improvement using innovation tools - Lizarbe, Jacqueline (2020)
This article describes a technique that uses innovation tools for process improvement aimed at providing new and better ways to apply methodologies, such as PDCA, Six Sigma, kaizen and jidoka, among others, that are currently used in companies. To this end, tools that involve employees of companies whose processes are not reaching the strategic objectives will be used. This methodology consists of six steps: the first three are focused on the definition, measurement and analysis of the problem, while the next three address the design, tests, and implementation and control of the solution. This tool seeks breakthrough results for companies during the process of analysis and implementation of improvements that result from applying the methodology described herein. Using the case method, the proposed methodology is applied to a real case and its results are validated.